(untitled) (African Journal of Biomedical Research, 2020)
Tuberculin skin test (TST) is among the screening criterion for tuberculosis and inflammation is known to be associated with Mycobacterium tuberculosis infection. Therefore, there is need to investigate the relationship between TST and inflammatory cytokines [tumour necrosis factor-alpha (TNF-α), interferon-gamma (IFN-γ)] and oxidative stress biomarkers [3-Nitrotyrosine (3-NT), inducible nitric oxide synthase (iNOS)] in apparently healthy Nigerian healthcare workers. Four millilitres of blood samples were collected from 34 participants for determination of TNF-α, IFN-γ, 3-NT and iNOS using ELISA. The TST was performed using 0.1 mL of 5 TU purified protein derivative and the diameter of induration was evaluated at 72 hours. Higher levels of TNF-α (10.10±4.31; 11.84±5.81; 12.95±6.96; 14.59±4.71 pg/mL) and IFN-γ (1.30±1.10; 1.44±1.25; 1.49±1.10; 2.10±1.56 pg/mL) were found at indurations of <5 mm, 5-9 mm, 10-14 mm, ≥15 mm, respectively. However, highest levels of 3-NT and iNOS, were found at indurations of 10-14 mm. Tuberculin skin test correlated positively with TNF-α, IFN-γ, iNOS (p>0.05) and age (p<0.05), while 3-NT was inversely correlated with TST (p>0.05). Almost half of the healthcare workers had indurations of ≥10 mm, suggestive of exposure to environmental Mycobacterium. This group of Nigerians should be made to undergo further diagnostic procedures for tuberculosis at regular intervals to establish that the positive TST is due to development of antibodies to Mycobacterium species but not as a result of actual infection.